Conehead Termite Nasutitermes corniger (Motschulsky) (Insecta: Blattodea: Termitidae: Nasutitermitinae) - Reina Tong; Katherine Tenn; Rudolf H Scheffrahn (EDIS)
The conehead termite, Nasutitermes corniger (Motschulsky) (Figure 1), is the first record of a non-endemic establishment from the family Termitidae in the United States (Scheffrahn et al. 2002). This widespread Neotropical species is unique among Florida termites due to the soldier’s nasus (an elongated frontal projection on the soldier’s head) and conspicuous nests (Scheffrahn et al. 2002). These termites are able to feed on many species of wood, i.e., structural wood and dead wood on living trees, and they inhabit a wide range of habitats. The conehead termite is of economic importance (Scheffrahn et al. 2014).